ZnO Thin-Film Transistors for Cost-Efficient Flexible Electronics - Vidor, Fábio Fedrizzi; Wirth, Gilson Inácio; Hilleringmann, Ulrich; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book describes the integration, characterization and analysis of cost-efficient thin-film transistors (TFTs), applying zinc oxide as active semiconductors.  The authors discuss soluble gate dielectrics, ZnO precursors, and dispersions containing nanostructures of the material, while different transistor configurations are analyzed with respect to their integration, compatibility, and device performance.  Additionally, simple circuits (inverters and ring oscillators) and a complementary design employing (in)organic semiconducting materials are presented and discussed.  Readers will benefit from concise information on cost-efficient materials and processes, applied in flexible and transparent electronic technology, such as the use of solution-based materials and dispersion containing nanostructures, as well as discussion of the physical fundamentals responsible for the operation of the thin-film transistors and the non-idealities of the device.
Chapter 1.Introduction -- Chapter 2.Fundamentals -- Chapter 3.Integration -- Chapter 4. Zinc Oxide Transistors -- Chapter 5.Electronic Circuits -- Chapter 6.Improvements -- Chapter 7.Conclusion and Future Perspectives.
Keywords: Electronic circuits; Electronics; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation